Bilateral proximal tibia fracture - Andriessen, M. J. G. (Springer-Verlag, 2010)
A bilateral fracture of the proximal tibia is rare in children. We describe a girl with a bilateral fracture just distal of the epiphyseal plate after minimal trauma.